Imperatives of forming economic security of territorial communities: digital and economic factors - Gonchar, Volodymyr (Ways to Improve Construction Efficiency, 2025)
The article explores the theoretical and methodological principles of forming economic security of territorial communities in the context of modern transformations of the socio-economic environment, caused by the processes of decentralization, digitalization, military and post-crisis challenges. The need to revise traditional approaches to interpreting economic security, which are reduced mainly to a financial-budgetary or resource-oriented understanding, is substantiated, and a comprehensive approach is proposed that integrates economic, institutional, infrastructural, digital and human-centric components of the security of territorial communities is proposed. Based on the analysis of scientific sources, modern scientific approaches to economic security at the macro, meso and micro levels are systematized, which made it possible to identify key factors influencing the stability of territorial communities in a dynamic and unstable environment. Particular attention is paid to the role of digital transformation of governance, institutional capacity of local governments, international governance standards and mechanisms for the restoration of territories as system-forming elements of the economic security of communities. The article identifies and summarizes the core imperatives for the formation of the economic security of territorial communities, among which the key places are occupied by institutional and international capacity, restoration and development resilience, integration of physical and infrastructure security with economic development, digital institutional resilience, economic adaptability and diversification, as well as a human-centric and socially networked component. It is proven that the economic security of communities is proactive in nature and should be considered not only as protection from threats, but also as the ability to restore, transform and long-term development. The author’s definition of the economic security of a territorial community is proposed as a dynamic state and the ability of a local socio-economic system to ensure sustainable functioning and development through the effective use of resource potential, management capacity, digital tools, preservation of human capital and social cohesion in conditions of crisis and post-crisis challenges. The practical significance of the results lies in the possibility of their use as a methodological basis for the development of development strategies and programs of economic security of territorial communities.